Dampak Kebijakan Ekonomi Publik Terhadap Pertumbuhan Ekonomi Daerah - Yahya, Muhammad Lutfi; Arifin, Waze Ridha Yushi; Irawan, Muhammad Naufal Fauzan; Rizwar, M Fahri; Rulvi, Vhamvilla; Fath, Muflih Saeful; Maharani, Dinda Fiachsania; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Public economic policy is an important instrument the government uses to regulate the economy to achieve social welfare goals. Public economic problems are problems of fulfilling the needs and welfare of the community. Related to the government's large role in ensuring welfare achievement, this study aims to analyze the impact of public economic policies on macroeconomic stability and the distribution of public welfare. This study uses a qualitative descriptive method with a literature study data collection technique. Literature studies enrich research literature so that conclusions can be drawn by reading articles in journals, books, and other media as reference sources. The success of public economic policies is highly dependent on effective planning, implementation, and supervision that is responsive to the socio-economic conditions of the community.